Subacute Lethal Bilateral Leg Time-Lag Infection by Streptococcus dysgalactiae - MD, Hiroki Nagasawa; MD, Youichi Yanagawa; PhD,; MD, Sei Kutsumi; MD, Ken-ichi Muramatsu; MD, Yoshihiro Kushida; MD, Ikuto Takeuchi; MD, Hiromichi Ohsaka; PhD,; MD, Kei Jitsuiki; MD, Kazuhiko Omori; PhD,; et al. (Archives of Clinical and Medical Case Reports, 2019)
A 66-year-old man felt left leg pain 7 days prior to admission to our hospital. His history included diabetes mellitus, hypertension, alcoholic live disease and chronic renal failure without hemodialysis. He drank 90 g of ethanol per day. As the pain gradually became exacerbated, he visited a local clinic on foot. The chemical laboratory analysis showed thrombocytopenia, so he was admitted to our department. On arrival, his consciousness was clear, and he had stable vital signs. He had bilateral lichen legs, and the left leg showed swelling, tenderness and redness. Computed tomography revealed a high-density area of soft tissue in the left leg. The patient was treated with meropenem and linezolid. On the second hospital day, he felt improvement of pain in his left leg, but began to feel pain in his right leg. He had oligouria. The same day, his blood pressure and respiratory function deteriorated, and both legs became red with purpura. He died on the third hospital day. Streptococcus dysgalactiae was detected in the blood and skin of his left leg cultures. We herein report a unique case of invasive Streptococcus dysgalactiae infection. Elderly patients with underlying diseases, who might have a soft tissue infection, may require early aggressive debridement of the infected tissue, in addition to performing prophylactic decontaminated measurements of the uninfected area.